Organization of Alkane Amines on a Gold Surface: Structure, Surface Dipole, and Electron Transfer - de la Llave, Ezequiel Pablo (2013)
Surface molecular self-assembly is a fast advancing field with broad applications in molecular electronics, sensing and advanced materials. Although a large number of practical systems utilize alkanethiols, there is increasing interest in alkylamine self-assembled monolayers (SAMs). In this article, the molecular and electronic structure of alkylamine SAMs on Au surfaces was studied. It was found that amine-terminated alkanes self-assemble, forming a compact layer with the amine headgroup interacting directly with the Au surface and the hydrocarbon backbone tilted by around 30° with respect to the surface normal. The dense layers formed substantially decrease electron tunneling across the metal/solution interface and form a dipole layer with positive charges residing at the monolayer/vacuum interface.